Effects of straw and herbicide application in the cowpea culture (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The objective of this research was to evaluate the yield of the cowpea crop, when grown on cover crops straws, managed or not with herbicides applied in post-emergence. The experiment was conducted in the field, in a complete randomized block design with three replications. In a 5x2 factorial scheme, five types of straw were tested: sorghum, ruziziensis grass, tanzania grass, marandu grass and weeds. The second factor was characterized by the absence and application of the ready mix of bentazone + imazamoxi at the dose 600 + 28 g ha-1 at 13 days after emergence and the herbicide haloxifope-p-methyl at the dose of 62.35 g ha- 1 to 18 DAE. Weed density and dry mass were evaluated at 20 and 85 DAE of the crop, plant height (AP), stem diameter, chlorophyll content, dry mass of stem, flowers, pods, leaves and aerial part and the leaf area in the flowering of the crop (46 DAE). At harvest, the production components were evaluated: number of grains per pod, number of grains per plant, weight one hundred grains, the population of cowpea plants and grain yield. The straws of grass-ruziziensis, grass-tanzania and grass-marandu on the soil surface reduce the dry mass of weeds, constituting necessary management where chemical control has not been carried out. Regardless of the use of straw, the application of the herbicide is essential to guarantee the productivity of the crop. The cultivation of cowpea on sorghum straw, ruziziensis grass, tanzania grass and marandu grass results in higher grain yield.